Application of modified-alginate encapsulated carbonate producing bacteria in concrete: a promising strategy for crack self-healing - Wang, Jianyun; Mignon, Arn; Snoeck, Didier; Wiktor, Virginie; Van Vliergerghe, Sandra; Boon, Nico; De Belie, Nele (Frontiers in Microbiology, 2015)
Self-healing concrete holds promising benefits to reduce the cost for concrete maintenance and repair as cracks are autonomously repaired without any human intervention. In this study, the application of a carbonate precipitating bacterium Bacillus sphaericus was explored. Regarding the harsh condition in concrete, B. sphaericus spores were first encapsulated into a modified-alginate based hydrogel (AM-H) which was proven to have a good compatibility with the bacteria and concrete regarding the influence on bacterial viability and concrete strength. Experimental results show that the spores were still viable after encapsulation. Encapsulated spores can precipitate a large amount of CaCO3 in/on the hydrogel matrix (around 70% by weight). Encapsulated B. sphaericus spores were added into mortar specimens and bacterial in-situ activity was demonstrated by the oxygen consumption on the mimicked crack surface. Specimens with free spores added showed no oxygen consumption. This indicates the efficient protection of the hydrogel for spores in concrete. To conclude, the AM-H encapsulated carbonate precipitating bacteria have great potential to be used for crack self-healing in concrete applications.